2019
DOI: 10.1039/c9cp01944h
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic evidence of a transition in ZIF-8 upon CH4 sorption

Abstract: We present the results of an experimental study of methane sorption in ZIF-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…104 For the flexible MOF ZIF-8 with rotational ligands, the sub-steps in the isotherms were the direct thermodynamic evidence of the structural transition induced by the guest molecules. 106,107 Gallaba et al explored the CH 4 adsorption in ZIF-8 over a low-temperature range and observed the clear substeps that corresponded to increasing uptake, which occurred during the structural switch of ZIF-8 from an original structure to a high-pressure one. 107 The non-vertical steps suggested the continuous transition of ZIF-8.…”
Section: Thermodynamic Modelling Of the Gated Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…104 For the flexible MOF ZIF-8 with rotational ligands, the sub-steps in the isotherms were the direct thermodynamic evidence of the structural transition induced by the guest molecules. 106,107 Gallaba et al explored the CH 4 adsorption in ZIF-8 over a low-temperature range and observed the clear substeps that corresponded to increasing uptake, which occurred during the structural switch of ZIF-8 from an original structure to a high-pressure one. 107 The non-vertical steps suggested the continuous transition of ZIF-8.…”
Section: Thermodynamic Modelling Of the Gated Adsorptionmentioning
confidence: 99%
“…106,107 Gallaba et al explored the CH 4 adsorption in ZIF-8 over a low-temperature range and observed the clear substeps that corresponded to increasing uptake, which occurred during the structural switch of ZIF-8 from an original structure to a high-pressure one. 107 The non-vertical steps suggested the continuous transition of ZIF-8. The presence of a broad peak in the isosteric heat of adsorption also implied a gate-opening transition.…”
Section: Thermodynamic Modelling Of the Gated Adsorptionmentioning
confidence: 99%